Spanish courts and Private international law: A problematic relationship - Ybarra Bores, Alfonso (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
Private international law is a branch of the legal system that has a greater impact in practice every day. The sources of this discipline are various: international conventions -multilateral and bilateral-, regulations of the European Union and internal laws of each State. The process of applying these rules, with its own methods and techniques, has become more complex every day. With this scenario, the Spanish courts continue making basic errors that could be understood in times when international legal traffic was not very common, but not nowadays. This article contains a criticism of the work of the Spanish courts in the application of the rules that regulate the various fields of private international law: international jurisdiction, applicable law, and recognition and execution of decisions.